The effect of menopause on lipoprotein (a) concentrations: A systematic review and meta-analysis - Anagnostis, Panagiotis; Antza, Christina; Trakatelli, Christina; Lambrinoudaki, Irene; Goulis, Dimitrios G.; Kotsis, Vasileios (Maturitas, 2023)
•Transition to menopause may increase lipoprotein (a) concentrations.•Whether this is attributed to the aging process or menopause per se cannot be clarified by current data.•Bilateral oophorectomy does not seem to affect lipoprotein (a) concentrations. Transition to menopause has been associated with an increased risk of cardiovascular disease (CVD), attributed mainly to atherogenic dyslipidemia. Whether lipoprotein (a) [Lp(a)], an independent cardiovascular risk factor, also contributes to menopause-associated CVD has not yet been clarified. The aim of this study was to systematically investigate and meta-analyze the best available evidence regarding the effect of menopause on Lp(a) concentrations. A comprehensive search was conducted in PubMed and Scopus databases up to March 8th, 2022. Data were expressed as weighted mean difference (WMD) with 95 % confidence intervals (CI). The I2 index was employed to assess heterogeneity. Seventeen studies were included in the qualitative and 15 in the quantitative analysis, yielding 4686 premenopausal and 8274 postmenopausal women. Lp(a) concentrations were lower in premenopausal than in postmenopausal women [WMD -3.77 (95 % CI -5.37, −2.18) mg/dl, p < 0.001; I2 99%, p < 0.001]. This difference was maintained when the analysis was restrained to good-quality studies (n = 9). Four studies included pre- and postmenopausal women, matched for age, and these found no difference in Lp(a) concentrations between groups [WMD -1.22 (95 % CI -3.15, 0.72) mg/dl, p < 0.001; I2 99%, p < 0.001]. Three studies provided data for Lp(a) in women before and after bilateral oophorectomy, and these found no difference between them [WMD -3.38 (95 % CI -7.29, 0.54) mg/dl, p = 0.09; I2 0%, p < 0.44]. Transition to menopause may increase Lp(a) concentrations, although the effect of aging cannot be excluded by current data.